7th International Conference for Young Chemists (ICYC 2019) - Pusat Pengajian Sains Kimia, PPSK (School of Chemical Sciences, Universiti Sains Malaysia, 2019)
Along with the celebration of USM Golden Jubilee in 2019, we bring you the most anticipated event in commemorating the 50 years of USM excellence in higher education. The International Conference for Young Chemists (ICYC) is a biennial conference organised by the postgraduate students of the School of Chemical Sciences, Universiti Sains Malaysia with the aim to gather local and international postgraduate researchers to create interaction and networking in the field of Chemistry. The idea of this conference started back in the year 2001 where it was known as the Regional Conference for Young Chemists (RCYC) targeting postgraduate researchers from the Asia Pacific Region (Malaysia, Singapore, Indonesia, the Philippines, India and Japan). What used to be the Regional Conference for Young Chemists (RCYC), has been rebranded into the International Conference for Young Chemists as we know it today. We are targeting postgraduate researchers from all around the world rather than just in this region. In fact, in August 2019, it is going to be the seventh time this international conference is going to be held